CLINICAL, GENEALOGICAL AND PSYCHOGENIC FACTORS IN THE GENESIS OF RECURRENT DEPRESSION - Maruta, N.O.; Kolyadko, S.P.; Fedchеnko V.Y.; Panko, T.V.; Cherednyakova, O.S.; Yaroslavtsev, S.O. (World of Medicine and Biology, 2021)
The survey covers the influence of inheritance endogenous mental disorders mechanisms, and the study of the genetics of depression. Significant risk factors for disease development are socio-economic and marital status (low social status correlates with an increase in mental pathology, particularly depression, and lack of family affects a person’s adaptive resources, is also a risk factor in the formation of mental disorders). Numerous psychotraumatic factors are also extremely significant for the initiation of any depression. Prospective studies have also confirmed the significance of chronic psychiatric trauma as predictors of recurrent course of the disease. The authors have highlighted interpersonal relationship disorders preceding depression exacerbate the effects of childhood trauma, contributing to the development of recurrent depression. In the absence of chronic stress in adults, the effect of childhood mental trauma was not significant.